COD reduction of simulated phenol wastewater using Fenton's reagent - Benjamin, Michael Francis D. (Animo Repository, 2005)
Advanced oxidation processes are processes that utilize highly reactive species to degrade organic pollutants in wastewater. These reactions can be accomplished through chemical and photochemical means. Advanced oxidation process is employed where conventional wastewater treatment methods are not effective due to the presence of refractory and bio-resistant compounds. Hydroxyl radicals (OH) are found to be the responsible species for degrading organic pollutants. There are many ways of producing these radicals. One pathway is using Fenton's reagent, which is a combination of hydrogen peroxide and iron (II) salts. The Fenton process is found to be effective in degrading and improving the biodegradability of organic pollutants, reducing wastewater toxicity, and reducing the chemical oxygen demand (COD) of industrial effluents. Phenol is an organic compound and a priority pollutant that is present in pharmaceutical wastewater and landfill leachate. It is also being used as a raw material in the production of household products such as disinfectants and mouthwashes. Its presence in our water bodies can cause serious impact in aquatic species and may cause potential risk to humans. Fenton's reagent can be used to degrade phenol since it exhibits resistance to biological treatment processes. This study utilized Fenton's reagent to reduce the COD of a simulated phenol wastewater. Typical process parameters such as effect of reactant dosage, effect of pH, and pH behavior were investigated. Two hundred (200) ppm of simulated phenol wastewater was investigated at different pH levels (2, 7, 9). Hydrogen peroxide (1000 Î¼l/L, 2500 Î¼l/L, 5000 Î¼l/L) and ferrous sulfate (125 mg/L, 250 mg/L, 500 mg/L) dosages were varied and mixed in the solution. The phenol degradation was measured in terms of the COD reduction of the solution using dichromate digestion method using a UV spectrophotometer. Results show that the Fenton process was effective at pH = 2. The increase in the H2O2 dosage from 1000 µl/L to 5000 µl/L and FeSO4 dosage of 125 mg/L to 250 mg/L resulted in a significant COD reduction of the simulated phenol wastewater. A 95% COD reduction was achieved using a H2O2 dosage of 5000 µl/L and FeSO4 dosage of 250 mg/L after 50 minutes of reaction time. Fenton's reagent is also capable of achieving 100% phenol degradation in aqueous solutions as verified by the gas chromatography analysis.